Value in the web of life, or, Why world history matters to geography. Issue 3 (November 2017) - Moore, Jason W
Critical geography as a field has yet to reckon with a fundamental geographical blind spot: the historical-geographical patterns of capitalism as a whole. There has been a steady—and studied—reluctance to grapple with capitalism as a historical-geographical place. A geography of value relations must proceed from the unities-in-diversity of capitalism's combined and uneven spatiality. If value relations are central to grasping the geographies of power, capital, and nature, those geographies are irreducibly world-historical. That does not mean imposed 'from above' in any straightforward sense. It means, as Marx and Engels perceptively observe, that value relations entwine everyday life with and within a mosaic of power and capital that operates at the scale of capitalism. Such an understanding situates value relations as unifying thread without positing linear causality or scalar primacy. Dialectical thinking about world history, after all, moves through variation—not in spite of it.